Botulinum toxin A decreases neural activity in pain-related brain regions in individuals with chronic ocular pain and photophobia - Reyes, Nicholas; Huang, Jaxon J.; Choudhury, Anjalee; Pondelis, Nicholas; Locatelli, Elyana V.; Felix, Elizabeth R.; Pattany, Pradip M.; Galor, Anat; Moulton, Eric A. (Frontiers in Neuroscience, 2023)
Introduction: To examine the effect of botulinum toxin A (BoNT-A) on neural mechanisms underlying pain and photophobia using functional magnetic resonance imaging (fMRI) in individuals with chronic ocular pain. Methods: 12 subjects with chronic ocular pain and light sensitivity were recruited from the Miami Veterans Affairs eye clinic. Inclusion criteria were: 1) chronic ocular pain; 2) presence of ocular pain over 1 week recall; and 3) presence of photophobia. All individuals underwent an ocular surface examination to capture tear parameters before and 4-6 weeks after BoNT-A injections. Using an event-related fMRI design, subjects were presented with light stimuli during two fMRI scans, once before and 4-6 weeks after BoNT-A injection. Light evoked unpleasantness ratings were reported by subjects after each scan. Whole brain blood oxygen level dependent (BOLD) responses to light stimuli were analyzed. Results: At baseline, all subjects reported unpleasantness with light stimulation (average: 70.8±32.0). 4-6 weeks after BoNT-A injection, unpleasantness scores decreased (48.1±33.6), but the change was not significant. On an individual level, 50% of subjects had decreased unpleasantness ratings in response to light stimulation compared to baseline (“responders,” n=6), while 50% had equivalent (n=3) or increased (n=3) unpleasantness (“non-responders”). At baseline, several differences were noted between responders and non-responders; responders had higher baseline unpleasantness ratings to light, higher symptoms of depression, and more frequent use of antidepressants and anxiolytics, compared to non-responders. Group analysis at baseline displayed light-evoked BOLD responses in bilateral primary somatosensory (S1), bilateral secondary somatosensory (S2), bilateral anterior insula, paracingulate gyrus, midcingulate cortex (MCC), bilateral frontal pole, bilateral cerebellar hemispheric lobule VI, vermis, bilateral cerebellar crus I and II, and visual cortices. BoNT-A injections significantly decreased light evoked BOLD responses in bilateral S1, S2 cortices, cerebellar hemispheric lobule VI, cerebellar crus I, and left cerebellar crus II. BoNT-A responders displayed activation of the spinal trigeminal nucleus at baseline where non-responders did not. Discussion: BoNT-A injections modulate light-evoked activation of pain-related brain systems and photophobia symptoms in some individuals with chronic ocular pain. These effects are associated with decreased activation in areas responsible for processing the sensory-discriminative, affective, dimensions, and motor responses to pain.